DETERMINANTS OF SUSTAINABILITY PRACTICE ADOPTION AMONG CULINARY MSMES: A SYSTEMATIC LITERATURE REVIEW USING THE ANTECEDENTS-DECISIONS-OUTCOMES FRAMEWORK - Yuneline, Mirza Hedismarlina; Yusoff , Mohd Nor Hakimin; Abdullah , Siti Salwani (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
Sustainability adoption among micro, small, and medium-sized enterprises (MSMEs) has become increasingly important for achieving environmental, social, and economic resilience. The culinary sector as a critical pillar of the MSME ecosystem plays as a vital source of revenue and employment, yet its current operational patterns contribute to environmental degradation. This study is a systematic literature review that examines the determinants influencing the adoption of sustainability practices among MSMEs. Using the PRISMA protocol, a total of 1,425 records were identified and screened, resulting in 89 peer-reviewed studies included in the final synthesis. The review employs the Antecedents-Decisions-Outcomes (ADO) framework to categorize the drivers of sustainability. Antecedents are shaped by internal awareness, social factors, and financial variables. These influence the Decision mechanisms, specifically attitude, subjective norms, perceived behavioural control, which ultimately determine the sustainability adoption as the primary Outcome. The findings reveal that sustainability adoption is influenced by antecedents that operate through the components of the Decomposed Theory of Planned Behaviour (DTPB) as a behavioural mechanism. Critically, this study demonstrates that digital financial inclusion acts as a catalyst by reducing information asymmetry and enhancing perceived behavioural control to navigate the complex trade-off of sustainability. While entrepreneurial orientation facilitates the conversion of stakeholder pressures and awareness into sustainable action. Theoretically, this study contributes by synthesizing the ADO and DTPB framework to provide understanding of the cognitive and environmental drivers of sustainability, specifically highlighting the moderating role of digital finance and entrepreneurial factors. Practically, the results suggest that policymakers should prioritize digital financial infrastructure to empower MSMEs, while managers can leverage entrepreneurial orientation to transform external regulatory pressures into competitive advantage. Despite progress, research gaps persist in sector-specific investigations within the culinary MSME context. Based on these insights, this study proposes a research agenda emphasizing behavioural, financial, and institutional mechanisms to advance sustainability adoption.